Bacteriophage AB-SA01 Cocktail in Combination with Antibiotics against MRSA-VISA Strain in an In Vitro Pharmacokinetic/Pharmacodynamic Model - Kebriaei, Razieh; Lev, Katherine L; Stamper, Kyle C; Lehman, Susan M; Morales, Sandra; Rybak, Michael J (Antimicrobial agents and chemotherapy, 2020)
This study aimed to test the efficacy of bacteriophage-antibiotic combinations (BACs) in 24-h time-kill settings and in simulated endocardial vegetation (SEV) pharmacokinetic/pharmacodynamic models for 96 h. BACs prevented the development of bacteriophage resistance, while some bacteriophage resistance emerged in bacteriophage-alone treatments. In addition, BACs resulted in an enhancement of bacterial eradication in SEV models. Our findings support the potential activity of BAC therapy for combating serious methicillin-resistant (MRSA) infections.